2012
DOI: 10.1039/c2sm26250a
|View full text |Cite
|
Sign up to set email alerts
|

Degradable emulsion-templated scaffolds for tissue engineering from thiol–ene photopolymerisation

Abstract: Further information on publisher's website:http://dx.doi.org/10.1039/c2sm26250aPublisher's copyright statement:Additional information: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
128
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 105 publications
(130 citation statements)
references
References 48 publications
(84 reference statements)
2
128
0
Order By: Relevance
“…The distribution of void diameters was wide in all cases, but within the range which has previously been used for cell culture. In common with earlier work we observe that heating the droplet phase (40 o C) increases both the average void size and distribution 16,22 ( Table 1, figure 4). Cell culture experiments with L929 cells showed that cells readily penetrated into and migrated through the structure as would be required for 3D cell growth ( Figure 5, 6).…”
Section: J Namesupporting
confidence: 75%
See 3 more Smart Citations
“…The distribution of void diameters was wide in all cases, but within the range which has previously been used for cell culture. In common with earlier work we observe that heating the droplet phase (40 o C) increases both the average void size and distribution 16,22 ( Table 1, figure 4). Cell culture experiments with L929 cells showed that cells readily penetrated into and migrated through the structure as would be required for 3D cell growth ( Figure 5, 6).…”
Section: J Namesupporting
confidence: 75%
“…Hexa--Acrylate and Triacrylate PolyHIPE Preparation. For comparison two biodegradable polyHIPEs reported by Caldwell et al based on a hexa--functional acrylate (DPEHA) and a second on a trifunctional acrylate (TMPTA) were also produced according to the previously published procedure 16 . The nominal porosity in each case was 85%.…”
Section: Synthetic Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…A study by Pierre et al employed EHA and IBOA monomers with trimethylolpropane triacrylate (TMPTA) crosslinker and Span 80 as surfactant, showing the effect of the monomer choice (EHA or IBOA) on the elastic properties of the monolith as well as employing photoinitiated polymerisation as a curing method [10] . Photoinitiated polymerisation reduces the cure time to seconds, which means that less stable emulsions can be cured which might otherwise destabilise during the long process of thermal curing or with increase in temperature [2,4,10,12] . This approach has potentially increased the versatility of PolyHIPE systems, and there is a growing interest in the use of photocurable monomers for their production [4,8,[11][12][13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%